Ag Journalism Training: Time for Another Look? - Bill Freiberg (Journal of Applied Communications, 1989)
This is in response to ACE Quarterly article "A Descriptive Study of Characteristics and Career Objectives of Agricultural Communications Students" published in issue No.3, Vol. 77.